Small field dose measurements using plastic scintillation detector in heterogeneous media. Issue 7 (21st May 2017) - Xue, Jinyu; McKay, Jesse D.; Grimm, Jimm; Cheng, Chee‐Wai; Berg, Ronald; Grimm, Shu‐Ya Lisa; Xu, Qianyi; Subedi, Gopal; Das, Indra J.
Abstract : Purpose: The purpose of this study was to evaluate a plastic scintillation detector for the measurement of small field dosimetry and to verify the accuracy of measured dose in comparison with Monte Carlo calculation in a heterogeneous medium. Methods: The study is performed with CyberKnife planning and delivery system. The setup consists of a custom made solid lung phantom with the insert of an Exradin W1 scintillation detector or an Exradin A16 ion chamber. The measurement was done for a series of cone sizes from 5 mm to 60 mm, and the dose was calculated by Monte Carlo algorithm in MultiPlan workstation. The difference between measurement and calculation was reported. Results: Our preliminary results demonstrated the applicability of plastic scintillation detectors in the measurement of small field dosimetry in a heterogeneous medium. The difference between the calculated and measured output factors was less than 3% for all cone sizes from 60 mm down to 5 mm. Without any corrections, the measured dose from the scintillation detector calibrated to the ion chamber reading was also within 3% of the Monte Carlo calculation in the lung phantom for cone sizes 20 mm or larger. Conclusions: Small field dosimetry is particularly relevant to stereotactic radiation treatment. The accuracy of dose calculation for small static beams is critical to dose planning so would potentially affect the treatment outcomes in a heterogeneous medium. Our results have shown good agreement with plastic scintillation detector in both homogeneous and heterogeneous medium.